(3MGTjI Ydi QSGFd GdTjN GdCfUGQjs - (3GdQhROQj,s ((3eMeO GdfLajs)
(3ChdgG (B:s
(3bhdg ajg NGJeI aj GdJYGOd hGdJQLjM(B...s
(3BNQgG (B:s
(3hHYHGQI KGdKI GdeaQhV EPG OGQ GdCeQ Hjf NHQjf CMOgeG eNGda ddYGeI hGdBNQ ehGab(B...s
(3JHUQI GdYfhGf (B:s
(3MGTjI Ydi QSGFd GdJYGOd hGdJQLjMs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3CUhd Gdabgs